A Discourse Analysis On Conversation Of “Who is The Ideal Presidential Candidate for Young People” On Mata Najwa - Ni Made Wilhel Mina Putri (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to understand and describe the model of speech from the results of interviews that occurred in the conversation